(untitled) (Aporte Santiaguino, 2024)
The purpose of the study was to determine the level of relationship that is evident between pre-professional practices and the quality of training of students of the professional career of Mining Engineering at the Santiago Antúnez de Mayolo National University (UNASAM), 2019. The type of study corresponds to quantitative, descriptive correlational and transactional research, whose design corresponds to simple descriptive correlational research. The sample was made up of 40 students of the professional career of Mining Engineering at UNASAM. The technique applied was the survey, whose instrument was the questionnaire. Descriptive and inferential statistics were used in the processing and analysis. The results indicate that there is a high positive direct relationship (r = 0.729) that is identified in the pre-professional practices and the quality of training of students. The coefficient of determination r2 = 0.5319. It is concluded that there is a direct and significant relationship between the variables of pre-professional practices and the quality of training in students of the Mining Engineering professional career at UNASAM, 2019. Therefore, for there to be quality in the training of students, pre-professional practices are essential.